Sistemas de transposição de peixes: contribuições para o design e monitoramento - Raoni Rosa Rodrigues (2015)
Fishways are structures created to mitigate the fragmentation of rivers, mainly caused by human interference. Although used throughout the world, these structures are not considered effective to re-establish the connectivity required to maintain many fish species. Among other things, part of this failure is due to the lack of knowledge about the biology and behavior of the species that use fishways, and part is due to inability to properly monitor and evaluate its functioning. Therefore, in this paper we seek to contribute to the reduction of these two gaps, assessing (1) the fish behavior in an open channel and their behavior related to flow speed and energy dissipation factor (EDF) and (2) the premises of three fish passage monitoring methods. For goal (1) an open channel was built on the banks of the Madeira River. We marked 512 fish of 20 species with PIT tags, and monitored their movements in the channel using radio frequency identification system. Two energy dissipaters were tested, and the hydraulic conditions were different between the tests. We used survival analysis tools to describe the behavior of fish inside the channel. The fish had better performance (less time, higher passage rates, higher percentage of successes) in flows with higher speed and EDF. The flow velocity was the variable with the greatest influence on the passage rate. The EDF was also important, but perhaps its effects are negligible. These results suggest that the analyzed species have better swimming performance and orientation skills in turbulent flow than those species that already had this behavior investigated. For the goal (2), we used an individual-based model simulating the behavior downstream of a dam of two hypothetical species of fish, which differ regarding their transit time within fish ladder: one with low transit time (mean < 4h) and other with high transit time (mean > 30h). The fish's behavior was influenced by the spillage flow and outflow from draft tube; it also responded to the time of day and the season of the year. Based on simulated results of 15 thousand individuals of each species in five different dams flow conditions, we estimated the fishway efficiency as the proportion of fish that reached the reservoir over the total of fish that arrived at the dam. We simulated the monitoring of the fish ladder with PIT tags in three scenarios (5, 10 and 20% of population being marked); with traps installed at the entrance and exit of the fish ladder in two consecutive days; and also the fish catch after drainage of fish ladder in five scenarios (1 3, 5, 10 and 20 days per month monitored). The results showed that monitoring with PIT tags was the only suitable method to evaluate the fish ladder efficiency for both species. The use of traps can be useful to monitor the efficiency of passage of the low transit time specie, but underestimates the passage of high transit time specie. Furthermore, traps can be used to assess the fish community using fish ladder, but just if used as long-term monitoring. Finally, fish catch after drainage underestimated the passage of the low transit time specie in all scenarios, thus overestimating the passage of high transit time specie. Those simulations suggested that the results obtained by various fish monitoring programs around the world may be biased, not characterizing properly the fish fauna using the fishways. Thus, it is needed to change the fishways monitoring methods, to better characterize the potential problems, enable the improvement of existing fishways and construction of new ones more appropriate to targeted species.